Pengaruh Gaya Hidup dan Citra Merek Terhadap Keputusan Pembelian Produk iPhone - Bambang Somantri; Ridha Afrianka; Fahrurrazi Fahrurrazi (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2020)
This study aims to identify and analyze the effect of lifestyle and brand image to purchase decision. The data used are primary data and secondary data obtained from questionnaires and literature. The population in this study are all students of SMAN 3 Sukabumi City that uses smartphone iPhone product. This research was conducted at SMAN 3 Sukabumi City, West Java-Indonesia. With sample size of 100 respondents drawn by purposive sampling method. The analytical method used is multiple linear regression analysis. Based on the research, the results of significance test the effect simultaneously with the F test, lifestyle and brand image together or simultaneously, have a significant effect on purchase decisions. Based on the test results of the partial effect by t test, that all independent variables, namely lifestyle and brand image have positive and significant impact on purchasing decisions.